Performance of Chara Chambelli Duck in Backyard System of Rearing at Adopted Village under NICRA at Darrang District of Assam (Indian Journal of Animal Production and Management, 2024)
The Chara Chambelli duck, indigenous to the  foothills of the Himalayas, has been gaining  attention for its potential as a valuable genetic  resource in small-scale poultry production systems.  This research paper aims to evaluate the  performance of Chara Chambelli ducks in backyard  rearing systems under agro-climatic condition of  Darrang district of Assam. In the context of the  NICRA project, the study was carried out on 400  Chara Chambelli ducks that were raised in  backyard systems at the NICRA adopted village of  Darrang district of Assam to look into their  environmental suitability, productivity, and financial  viability. By the time the ducks reached their fifth  month of life, the overall weight of the male and  female was measured at 1480.02 ± 18.14 grams  and 1365.46 ± 14.90 grams respectively. The duck  was 155.03± 9.18 days old on average when it laid  its first egg. The data showed that the annual  production of eggs was 169.12± 6.04 numbers and  the weight of eggs at 63.98 ± 2.84 grams. For ducks  and drakes, the corresponding benefit-cost ratios  were 2.26 and 1.80. It was found that rearing Chara  Chambelli ducks in backyard systems with low input  traditional systems is more cost-effective than  raising Assamese native ducks. Results indicate  that Chara Chambelli ducks exhibit promising  performance characteristics suitable for backyard  rearing, contributing to sustainable livelihoods and  biodiversity conservation efforts.
Keywords: Chara Chambelli duck; backyard rearing; performance evaluation; small-scale poultry production; NICRA